Penguatan Iptek dan kearifan lokal dalam pengelolaan perikanan di Desa Pangkalan Jambi Kecamatan Bukit Batu Kabupaten Bengkalis - Dadang Mashur; Ridwan Manda Putra; Herman Herman; Mayarni Mayarni; Mimin Sundari Nasution; Eka Hariyani; Musadad Musadad; Risky Arya Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
The coastal area has many potential resources whose utilization is not optimal. One potential that must be developed is the potential of human resources, with ability and creativity, humans can create and develop everything that is initially not considered and has a low selling value into something that has high economic value. The strengthening of science and technology aims to motivate rural communities, especially fishermen, to develop creativity so that they can increase the income and welfare of fishing communities. The science and technology strengthening activity was carried out in Pangkalan Jambi Village with two models, namely the application of the Center for Environment and Society Model, namely utilizing the productive use of social capital and environmentally friendly management of fisheries resources. The second application is the Entrepreneurship Capacity Building (ECB) model related to the ability of the entrepreneurial community. Science and technology strengthening activities and local wisdom in the form of fostering fishing communities in the management of fishery products such as chips, nuggets, meatballs, oil, as medicines and fish jelly as cosmetics. Then institutional development and assistance for marketing. So far, fishermen are only able to sell their catches directly without technology-based processing. After the dedication, there were three programs carried out including the formation of individual skills in fish processing, group formation, and marketing management assistance.